Planning and implementation of a rapid response manufacturing facility through cost effective electronic commerce - Sia, Yin Hua. (2011)
The Internet has made it very easy to find any information at any time. This together with the rapid advance of information technology and the falling cost of PCs accentuated influence of Internet worldwide. In this respect, the Internet provides an excellent opportunity for business organizations to reach-out to more customers worldwide. Organizations could achieve this target by shifting their business focus to the Net and embrace electronic commerce.